Validation of Controlled Attenuation Parameter Measured by FibroScan as a Novel Surrogate Marker for the Evaluation of Metabolic Derangement - Huang, Zhimin; Ng, Kaka; Chen, Hongyan; Deng, Wanping; Li, Yanbing (Frontiers in Endocrinology, 2022)
Background/Objectives: Renaming non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated fatty liver disease (MAFLD) suggests a shift of emphasis to the accompanying metabolic disturbance. Controlled attenuation parameter (CAP) measured by FibroScan has been shown to be correlated with hepatic steatosis. We aim to validate its usefulness as a novel surrogate marker for evaluating metabolic derangement. Subjects/Methods: Volunteers were recruited from medical staff at our hospital to undergo CAP measurements. Anthropometrics, CAP and laboratory assessment for metabolic profiles and insulin resistance were collected. CAP < 238 dB/m denoted no hepatic steatosis, 238 ≤ CAP ≤ 259 dB/m as mild, 260 ≤ CAP ≤ 291 dB/m as moderate, and CAP > 291 dB/m as severe hepatic steatosis according to previous reports. Results: Data of 824 participants were included for analysis. The age was 53.2 ± 15.4 years, BMI was 23.6 ± 3.1 kg/m2, 24.4 % were male subjects, 22.0 % met the criteria for metabolic syndrome (MetS). Taking the group with CAP < 238 dB/m as control, subjects with mild, moderate and severe hepatic steatosis had increased odds of MetS by 3.51, 3.32, 5.12 folds after adjusting for multiple confounders (p = 0.020). Metabolic profiles, insulin resistance and presence of MetS were similar between normal-weight subjects with CAP ≥ 238 dB/m and overweight subjects with CAP < 238 dB/m. Even in subjects with no MetS components, those with CAP ≥ 238 dB/m had higher BMI, waist circumferences, uric acid, triglyceride, white blood cell count, insulin resistance, whereas lower adiponectin and estimated glomerular filtration rate. Waist circumference [OR 1.11 (1.04, 1.18), p = 0.001] and HOMA-IR [ OR 2.39 (1.18, 4.83), p = 0.016] were predictive of hepatic steatosis according to CAP ≥ 238 dB/m. Conclusions: Controlled attenuation parameter is a convenient, sensitive and non-invasive indicator for metabolic derangement. Prospective studies are needed to further validate its usefulness as a surrogate marker for transition of metabolic status over time.